2021
DOI: 10.1590/0001-3765202120191462
|View full text |Cite
|
Sign up to set email alerts
|

Exotic species are perceived more than native ones in a megadiverse country as brazil

Abstract: Research on environmental perception is essential for the understanding of individuals' relations and expectations towards natural environments. Here, we evaluated the perception of high school students on exotic and native species in Brazil. We interviewed 371 students from two high schools located in the state of Goiás, one with and one without a protected area within its premises. Students needed to identify native and exotic species and to indicate species origin. We used a t-test to evaluate differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…Similarly, Sampaio et al (2018) observed a greater knowledge about native animals among children who had contact with nature. In fact, the experiences people have with nature are considered a key factor to determine how they will establish connections with nature and how they will perceive it (Carvalho, 2014;Melo et al, 2021). Unsurprisingly, this does not seem to be the case of the surveyed area, given that 94.27% of the population lives in urban areas (Instituto Brasileiro de Geografia e Estat ıstica (IBGE), 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Sampaio et al (2018) observed a greater knowledge about native animals among children who had contact with nature. In fact, the experiences people have with nature are considered a key factor to determine how they will establish connections with nature and how they will perceive it (Carvalho, 2014;Melo et al, 2021). Unsurprisingly, this does not seem to be the case of the surveyed area, given that 94.27% of the population lives in urban areas (Instituto Brasileiro de Geografia e Estat ıstica (IBGE), 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the wide geographic distribution of these species, with their presence in several Brazilian phytogeographic domains, contributes to knowledge among students. For instance, the Jaguar is one of the best-known native species among university students from other Brazilian regions (de Melo et al, 2021). Besides, the Brown-throated Sloth is known as the world's slowest animal, so in simplified vocabulary, it is a synonym of a person who has no disposition to work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brazil has different climate (Alvares et al 2013 ) and biodiversity hotspots (Begossi et al 2000 ), in which the dynamic of interactions between birds and their resources may be highly complex (e.g., Campagnoli and Christianini 2022 ) even in human-modified landscapes (Pizo 2007 ). Besides, Brazilians have different cultures, social characteristics, and perceptions of their fauna (Belaire et al 2015 ; Melo et al 2021 ). Consequently, the extrapolation of conclusions suggested by foreign studies is still mistrusted by Brazilian citizens and decision-makers, inciting controversial discussions on the encouragement or the banning of the use of bird feeders in the country (e.g., Olmos 2017 ; Baverstock et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%